Spatial Measurements on USGS Topo Maps - Hartwig Hochmair; Adam Benjamin (EDIS, 2021)
United States Geological Survey topographic maps provide a variety of geospatial measurement tools thanks to their built-in georeferencing capabilities. Georeferencing facilitates display of geographic coordinates and measurement of distances, perimeters, and areas on PDFs using the measure tools built into Adobe Reader and Adobe Acrobat. This 7-page fact sheet written by Hartwig H. Hochmair and published by the UF/IFAS School of Forest Resources and Conservation explains and showcases the use of these geospatial readout functions. It also provides background information about and assistance with estimating point coordinates on the Universal Transverse Mercator grid cast on USGS topographic maps as an optional layer.